2004
DOI: 10.1542/peds.113.5.e504
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Pseudoobstruction in Kawasaki Disease

Abstract: ABSTRACT. Intestinal pseudoobstruction is an uncommon but important manifestation of Kawasaki disease. Its occurrence at the onset or during the course of the disease may confuse the clinical picture and cause delay in diagnosis and treatment. This delay may be responsible for the high rate of coronary artery abnormalities that have been reported in patients with this complication. We suggest that Kawasaki disease be considered in the differential diagnosis of any child presenting with intestinal pseudoobstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Its occurrence varies from 1.4% to 2.6% in two large cohorts of children with KD . Moreover, intestinal pseudo‐obstruction at presentation has been reported as single case reports . From literature it appears that intestinal involvement in KD requires conservative management, as it simulates intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its occurrence varies from 1.4% to 2.6% in two large cohorts of children with KD . Moreover, intestinal pseudo‐obstruction at presentation has been reported as single case reports . From literature it appears that intestinal involvement in KD requires conservative management, as it simulates intestinal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Moreover, intestinal pseudoobstruction at presentation has been reported as single case reports. 7,8 From literature it appears that intestinal involvement in KD requires conservative management, as it simulates intestinal obstruction. Conversely, surgery should be reserved for true intestinal obstruction presenting with clinical and radiological peritoneal signs.…”
Section: Key Pointsmentioning
confidence: 99%
“…One case by Akikusa et al, demonstrated KD as the underlying pathology mimicking mechanical intestinal obstruction, making KD a differential consideration in pediatric patient presenting with a fever of unknown cause and abdominal pain. 45 This "pseudo-obstruction" as described was portrayed to be the sequelae of the inflammation ensued by KD causing bowel ischemic changes. 45 In the acute setting, conservative management with high dose IV gamma globulin and aspirin can curtail symptoms and long-term complications.…”
Section: Kawasaki's Diseasementioning
confidence: 99%
“…45 This "pseudo-obstruction" as described was portrayed to be the sequelae of the inflammation ensued by KD causing bowel ischemic changes. 45 In the acute setting, conservative management with high dose IV gamma globulin and aspirin can curtail symptoms and long-term complications. Invasive intervention is reserved as a last resort to prevent or treat vascular or aneurysm rupture and maintain blood flow to prevent severe end organ ischemia or infarct.…”
Section: Kawasaki's Diseasementioning
confidence: 99%
“…(Fig 6a and specific imaging finding, as it can occur with other acute illnesses as well. Other abdominal manifestations that have been reported in KD and could potentially confuse the clinical picture include intestinal pseudo-obstruction, focal colitis, bowel infarction, and bowel stricture secondary to ischemia (30). Although involvement of the coronary arteries is the most characteristic manifestation of KD, other medium-sized muscular arteries also may be involved (Fig 7).…”
Section: Kawasaki Diseasementioning
confidence: 99%